Electronic Contracts and E-Signatures in Indonesia: Legal Framework and Challenges in the Digital Revolution - Hasan, Laura Kurniadi; Putra, Moody Rizqy Syailendra (CV. Rayyan Dwi Bharata, 2025)
This paper explores the legal framework and challenges surrounding the implementation of electronic contracts and e-signatures in Indonesia, particularly in the context of the digital revolution. It delves into the evolving contract law under the influence of digitalization, highlighting the critical aspects of Law No. 11 of 2008 (ITE Law) and Government Regulation No. 71 of 2019. The paper addresses the legal requirements for valid electronic contracts, the role of certified and uncertified e-signatures, and the complexities involved in their enforcement. It also identifies key challenges, such as technology-neutrality, cross-border recognition, and the role of certification authorities, that affect the integration of Indonesia's legal framework with global standards. The findings emphasize the need for further legal reforms to enhance the security, flexibility, and reliability of electronic agreements, supporting Indonesia’s digital economy.